Bilateral Nevus of Ota Treated with Combination of CO2 Fractional Laser and 1064 nm Nd:YAG Laser - Dewi Nurasrifah; Iskandar Zulkarnain (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Ota’s nevus (nevus fuscocaeruleus ophthalmomaxillaris) was first described by Ota in 1939. It is characterized by blue–black or gray–brown dermal melanocytic pigmentation and typically occurs in areas innervated by the first and second branches of the trigeminal nerve. Mucosal pigmentation may occur involving conjunctiva, sclera, and tympanic membrane (oculodermal melanocytosis), or other sites. Purpose: Describe the clinical manifestation and therapy of bilateral nevus of Ota. Case: A 20-year-old female patient, complaint about dark patches in both of her cheek and forehead since birth. Histopathology has not been done because patient refused to do the biopsy. Diagnosis of bilateral nevus of Ota is made based on anamnesis and clinical manifestations. Discussion: Pasien has undergo Nd:YAG laser session for Ota’s nevus and the result was not satisfactory. Now patient was given combination laser of CO2 fractional laser and 1064 nm Nd:YAG laser for 4 sessions with 3 months interval. After four laser sessions, there has been an improvement in the lesions as the lesions is getting lighter. The purpose of CO2 fractional laser is to increase light delivery into the tissue and for extruding material out of the skin. This laser combination aimed to increase the ability to remove pigment as an alternative method without inducing a systemic allergic reaction. Conclusion: Nevus of Ota is diagnosed based on clinical finding. Combination therapy of CO2 fractional laser and1064 nm Nd:YAG is the mode of choice because of excellent results.